PROBLEMATIKA PUTUSAN PIDANA PENGAWASAN: TINJAUAN KEKOSONGAN PARAMETER PEMIDANAAN DAN KONSEKUENSI EKSEKUTORIAL BERDASARKAN UU NOMOR 1 TAHUN 2023 - Abdul Rahman; Yudi Krismen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The reform of the criminal justice system through Law No. 1 of 2023 on the National Criminal Code has brought fundamental changes to the adjudication stage, particularly a paradigm shift in judicial decisions from retributive to restorative through the instrument of Probation. This study aims to analyze the legal issues in the process of determining probation sentences due to the absence of Sentencing Guidelines, as well as to examine the institutional readiness of the Correctional Institution (BAPAS) in implementing these sentences in the field. This normative legal study employs a legislative and conceptual approach, relying on the analysis of both primary and secondary legal materials. The findings indicate that the absence of measurable technical sentencing guidelines results in judges’ discretionary authority becoming overly broad, thereby creating a risk of discriminatory disparities in rulings for cases with similar characteristics. Furthermore, court rulings imposing non-custodial sanctions risk losing their enforceability due to a shortage of Probation Officers and inadequate BAPAS facilities, which ultimately reduces the meaning of supervision to a mere administrative formality. As a solution, this study recommends the issuance of implementing regulations that strictly mandate the use of the Pre-Sentence Report as an objective basis for consideration before a judge issues a ruling.